Design of Data Warehouse for Monitoring Hotel’s Food and Beverage Cost - Putu Risanti Iswardani; I Wayan Surya Pramana; Komang Oka Saputra (International Journal of Engineering and Emerging Technology, 2019)
Monitoring is a mandatory process which carried out in every company. Through monitoring process, each business processes within company can be controlled more properly, problems that might occur in the business process can be anticipated, and company’s revenue can be optimized. However, based on survey conducted in some hotels, it is found that there is over-budget problem in food and beverage costs due to difficulties in monitoring process. Therefore, this study aims to design a data warehouse that can help to optimize monitoring process of hotel’s food and beverage costs. Design of proposed data warehouse was built using nine step design methodology developed by Kimball & Ross. Furthermore, proposed data warehouse design was assessed using feasibility assessment of Likert scale. Based on assessment results, it is known that, the proposed data warehouse design has feasibility value of 84%, which is shows that respondents agreed with the design